Molecular Monopoly for Genetics teaching (Research, Society and Development, 2021)
Molecular Monopoly is a board game proposal to develop students learning Genetics concepts, who will work in groups and exchange information with each other. The challenge is to answer the game's questions correctly, earn the most coins, and buy nucleotides to form the largest DNA molecule. The greater the amount of coins purchased, the greater the number of nucleotides and, consequently, the possibility for the group to win the game, and improve their knowledge of the Genetics topics addressed. In this study, we present our educational product for teaching Science and Biology, as well as evaluating the gameplay of this board. Thus, Molecular Monopoly proved to be a good material for teaching and that contributes to the creative and motivating process in teaching and learning about certain concepts of Genetics in high school. This game proposal contributed to the collective construction of knowledge, as well as the development of other relevant skills for the formation of a student, such as teamwork, leadership and collaboration. Thus, we conclude that the game meets its proposal, as it is a facilitating and playful didactic tool for the teaching of Genetics and also contributes as a teaching methodological alternative in view of the various possible applications.